Morpho-molecular characterization of Lasiodiplodia theobromae (Pat.) Griffon & Maubl and its first report on the association with coconut kernel from Bangladesh (Bangladesh Journal of Plant Taxonomy, 2025)
This study marks the first report of Lasiodiplodia theobromae associated with coconut in Bangladesh, a pathogen known to cause wide range of diseases crippling coconut production worldwide. Two isolates, Lt_BD 1 and Lt_BD 4, were obtained from coconut samples and subjected to comprehensive morpho-molecular and phylogenetic analyses. Morphological observations, including colony characteristics (color, texture, and surface appearance), growth patterns and conidial dimensions and shapes, preliminarily identified the isolates as Lasiodiplodia species. Molecular analysis, through PCR amplification of the internal transcribed spacer (ITS) regions, confirmed the identity of the isolates as L. theobromae. A phylogenetic tree, constructed using sequences of the studied isolates alongside 48 reference Lasiodiplodia species (retrieved from NCBI) and one out-group species (Pyricularia oryzae), corroborated this identification. This study provides a foundation for further rigorous research on the diseases of coconut caused by L. theobromae in Bangladesh.Bangladesh J. Plant Taxon. 32(1): 105-113, 2025 (June)